Long-term monitoring of fish in a freshwater reservoir: Different ways of weighting complex spatial samples - Tesfaye, Gashaw C.; Souza, Allan T.; Bartoň, Daniel; Blabolil, Petr; Čech, Martin; Draštík, Vladislav; Frouzová, Jaroslava; Holubová, Michaela; Kočvara, Luboš; Kolařík, Tomáš; Martinez, Carlos; Moraes, Karlos R.; et al. (Frontiers in Environmental Science, 2022)
Anthropogenic activities continue to pose the greatest challenges to freshwater ecosystems. Therefore, long-term monitoring is essential for the management and conservation of these resources. Monitoring programs for freshwater bodies often use a range of indicators, including biological elements such as fish. Existing European standard provides a depth-stratified gillnet sampling approach mainly in benthic habitats and at the deepest part of lakes to account for the uneven distribution of fish. However, the commonly used CEN (European Committee for Standardization) protocol does not weight sufficiently habitat volumes and underrepresent pelagic habitats to calculate whole-lake catch and biomass per unit effort (CPUE and BPUE, respectively). Modified European standard gillnet (extended by 4 larger mesh-sizes in the geometric series) catch data collected over 18 years (2004 - 2021) in Římov Reservoir (Czech Republic) were used for a method comparison on indices for relative abundance and biomass of fish: one non-weighted approach (CEN protocol) and two volume-weighted approaches. We also evaluated changes in species composition and trends in these fish population and community indices over time. Results indicated interannual changes in species composition, relative abundance, and biomass of fish community. The CEN protocol tended to put greater emphasis on benthic habitats which generally have larger CPUE and BPUE. Consequently, the two volume-weighted approaches produced lower estimates of the two parameters. All approaches consistently showed an increasing trend in fish abundance and a decreasing trend in biomass over the study period, which is substantiated by the observed declining trend in the mean weight of the predominant fish species. Following our assessment, we put forward the new volume-weighted approach as the most realistic approximation of fish populations and therefore recommend its use, especially for large lakes and reservoirs.